ANALISIS PENERAPAN AKUNTANSI PADA KOPERASI KONSUMEN PEGAWAI REPUBLIK INDONESIA XYZ - Putri, Veronika Anggia; Saputra, Dian (Journal Of Islamic Finance And Accounting Research, 2023)
This research was conducted at the XYZ Republic Of Indonesia Employee Consumer Cooperative. This study aims to determine whether the application of accounting ar cooperative is in accordance with generally accepted accounting principles. The data used are primary data an secondary data. Data collection techniques used are interviews and documentation. Several deficiencies can be found in this study, some of these deficiencies ar that cooperatives places risk fund accounts in current liabilities, and cooperatives do not explain reserve funds in the Notes To Conslidated Financial Statements. After conducting research on cooperative, it can be concluded that the application of accounting to the XYZ Republic Of Indonesia Employee Consumer Cooperative is not accordance with generally accepted accounting principles.